Antibacterial Screening of Epidermal Mucus Extracts of Two Bornean Barbodes Fishes - Yang, Lee (UNIMAS, 2023)
Fish are in constant interaction with their microbe-rich habitat. Fish epidermal mucus constitutes the first line of defence against its aquatic environment as it contains a wide range of innate immune components, including antimicrobial proteins. Currently, freshwater fish receives less attention from researchers compared to their marine counterparts. Furthermore, knowledge about native fish from Borneo remains scarce. Therefore, the study was aimed to establish better understanding on the epidermal mucus of two Bornean freshwater fish species Barbodes sealei and Barbodes everetti. In the study, protein recovery of five different mucus extracts with different solvents and concentrating methods namely Freeze-dried Crude (distilled water) extract (FDC), Freeze-dried Aqueous (saline) extract (FDS), Freeze-dried Acidic (3 % acetic acid) extract (FDA), Ammonium-sulphate-precipitated Aqueous (saline) extract (APS), and Ammonium-sulphate-precipitated Acidic (0.8 % acetic acid) extract (APA), was compared. Subsequently, antibacterial properties of the epidermal mucus extracts against selected bacterial strains were determined. Aiding by Liquid Chromatography with Tandem Mass Spectrometry (LC-MS/MS), major proteins from the active extracts were identified and the antibacterial proteins were also determined. For both species, the results revealed higher protein contents in AP mucus but better recovery in FD mucus. Higher protein contents could be associated with the higher level of stress experienced by fish specimens while better protein recovery might be due to minimal number of sample transfer during extract preparation. Next, four bacterial strains namely Listeria monocytogenes ATCC 7644, Pseudomonas aeruginosa ATCC 27853, Salmonella braenderup ATCC BAA 664, and Vibrio cholera were sensitive towards four out of five extracts from both species as well. Interestingly, FD acidic extract of B. sealei exhibited antibacterial activity at low protein concentrations (3.57 ± 0.5 µg/ml). The findings of present study set a foundation for future antibacterial studies of fish epidermal mucus and provide interesting new avenues of research in exploring the antimicrobial potential of fish epidermal mucus.